2021
DOI: 10.3389/fendo.2021.772349
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Endocrine Status, Tumor Hypoxia and Immunogenicity for Therapy Success in Epithelial Ovarian Cancer

Abstract: Epithelial ovarian cancer is predominantly diagnosed at advanced stages which creates significant therapeutic challenges. As a result, the 5-year survival rate is low. Within ovarian cancer, significant tumor heterogeneity exists, and the tumor microenvironment is diverse. Tumor heterogeneity leads to diversity in therapy response within the tumor, which can lead to resistance or recurrence. Advancements in therapy development and tumor profiling have initiated a shift from a “one-size-fits-all” approach towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 214 publications
(226 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, recent studies demonstrated that MCT4 expression is triggered by hypoxia and mediated by HIF-1α, while MCT1 expression is not enhanced in this case [ 45 ]. Highly hypoxic areas are usually increased in large tumor lesions, along with inadequate blood flow and ascites in the tumor milieu [ 6 ]. Therefore, HIF-1α can be a plausible factor contributing to resistance to carboplatin via alterations in cancer cell metabolism by enhanced MCT4 expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies demonstrated that MCT4 expression is triggered by hypoxia and mediated by HIF-1α, while MCT1 expression is not enhanced in this case [ 45 ]. Highly hypoxic areas are usually increased in large tumor lesions, along with inadequate blood flow and ascites in the tumor milieu [ 6 ]. Therefore, HIF-1α can be a plausible factor contributing to resistance to carboplatin via alterations in cancer cell metabolism by enhanced MCT4 expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-grade serous carcinoma (HGSC) is the most common subtype, accounting for over 70% of epithelial ovarian cancers (EOCs). The hallmark feature of HGSC is the diversity in the morphology of different cancer cells, depending on their intratumoral spatial localizations and the tumor microenvironment [ 6 ], leading to widely diverse drug resistance mechanisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…OCSC niches are very specific because of the inflammatory and immunosuppressive milieu of the peritoneal cavity, where OC implants show exceptional tropism towards fatty tissue (omentum, colon appendices) and highly vascularized peritoneal immune collections called milky spots, which are followed by the production and accumulation of ascites [ 397 , 398 ]. Ascites is rich in immunosuppressive cytokines and contains increased numbers of immune tolerant PD-1 and CTLA-4 expressing T cells [ 399 , 400 ]. This unique environment also plays an important role in the creation of specific TIME where several immune cell types, including TAMs, TANs, DCs, Tregs, and MDSCs cells support tumor progression, chemoresistance, and immune evasion [ 401 ].…”
Section: Ocscs and Escape From The Host Immune Surveillancementioning
confidence: 99%
“…Pyruvate dehydrogenase kinase 1 activity inhibits pyruvate dehydrogenase, contributing to a shortage of pyruvate availability for the tricarboxylic acid cycle [ 17 ]. In turn, this lack of pyruvate decreases mitochondrial oxygen consumption and increases intracellular oxygen availability, to ultimately promote tumor cell survival [ 18 , 19 ]. Additionally, tumor cells have altered mitochondrial gene expression, including increased ubiquinol-cytochrome C reductase complex assembly factor 3 expression, which contributes to increased hypoxia by promoting a positive feedback loop with mitochondrial reactive oxygen species (ROS) to stabilize HIF-1α expression and enhance glycolysis [ 20 ].…”
Section: Cellular Metabolism Of Normal and Cancerous Cellsmentioning
confidence: 99%
“…As tumor heterogeneity causes significant disparities in therapeutic responses within the tumor, often leading to recurrence or resistance [ 19 ], it is critical to understand these unique components of the tumor from a therapeutic perspective to optimize therapy efficacy. To take advantage of the addition of a statin to boost cancer therapeutic strategies, we must optimize and better understand the myriad of variables influencing statin drug efficacy.…”
Section: Considerations When Targeting Cancer Metabolism With Statinsmentioning
confidence: 99%